2021
DOI: 10.1136/lupus-2021-000513
|View full text |Cite
|
Sign up to set email alerts
|

Lupus clinical trial eligibility in a real-world setting: results from the British Isles Lupus Assessment Group-Biologics Register (BILAG-BR)

Abstract: ObjectiveTo quantify how well phase III randomised clinical trials in both SLE and lupus nephritis (LN) represents a real-world SLE cohort.MethodsLiterature reviews were performed of major published phase III SLE (n=12) and LN (n=6) clinical trials (ClinicalTrials.gov). Inclusion and exclusion criteria common across these trials were collated for non-renal SLE or LN trials, and applied to patients recruited to the British Isles Lupus Assessment Group-Biologics Register (BILAG-BR) starting either biological or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Indeed, it has been shown that nearly two-thirds of patients are ineligible to participate in non-renal SLE clinical trials. 64 In particular, the inclusion limitations in clinical trials are greatly influenced by authorised standard-of-care treatments, prior treatments and, especially, the washout periods for various treatments. Of note, some trials have suggested that background immunosuppressants could be safely withdrawn in patients with SLE with active but non-organ-threatening flare to support more interpretable trial results.…”
Section: Additional Perspectives For Improving Sle Trialsmentioning
confidence: 99%
“…Indeed, it has been shown that nearly two-thirds of patients are ineligible to participate in non-renal SLE clinical trials. 64 In particular, the inclusion limitations in clinical trials are greatly influenced by authorised standard-of-care treatments, prior treatments and, especially, the washout periods for various treatments. Of note, some trials have suggested that background immunosuppressants could be safely withdrawn in patients with SLE with active but non-organ-threatening flare to support more interpretable trial results.…”
Section: Additional Perspectives For Improving Sle Trialsmentioning
confidence: 99%
“…Increasingly complex inclusion/exclusion criteria with many restrictions related to the past medical history, biologic use prior to enrollment, and laboratory tests have led to further reduction in the number of eligible patients in clinical trials. [ 18 ] Inclusion criteria usually specifies a disease activity in the moderate to severe range; however, exclusion criteria restrict the range of disease activity by limiting use of steroids or other immunosuppressive treatments. [ 19 , 20 ] More medications have been approved for SLE and the standard of care treatment is evolving but inclusion/exclusion mostly remains the same, and as such more patients are excluded from studies.…”
Section: Trial Design Challengesmentioning
confidence: 99%
“…Using data from two international RCTs, we previously reported associations between obesity and clinically important impairments in physical aspects of HRQoL, fatigue, and social functioning [ 15 ]. Despite the large sample size and ethnical diversity of the patients included, this does not necessarily resemble the target population in a real-world setting, as most individuals from clinical practices do not meet the eligibility criteria for RCT programmes [ 17 ].…”
Section: Introductionmentioning
confidence: 99%